Martha Jane Dalzel Riggs: An American missionary wife in the nineteenth-century Ottoman Empire - Korkmaz, Melisa. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
This thesis explores the little known activities and writings of Martha Jane Dalzel Riggs, a missionary wife operating under the American Board of Commissioners for Foreign Missions (ABCFM), during her active years from 1832 through 1887, initially spent in Greece, and then mostly in the Ottoman Empire. Drawing from her family archives and other primary sources, the thesis aims to demonstrate the significance of Riggs’ contributions to the American Board and its network, and to question the boundaries between her roles as a qualified missionary, a mother and a wife from a historical perspective. Mission work for females, taking its cue from the nineteenth-century American domestic discourse, of which Riggs is a leading example, connected education at home to the character of a nation. Correspondingly, the thesis uncovers the rich content of her letters, the subjects of which are domestic matters such as family, well-being and the education of her children and missionary matters both woven together. The thesis also highlights her detailed observations of her stays in several countries for historians wanting to better understand the events and changes in the world in the nineteenth century, especially in the Ottoman Empire. From a broader perspective, zooming out from the specific lives of Martha Jane Dalzel Riggs and other female missionaries, the thesis suggests the need to reevaluate the impact of missionary wives and, eventually, women in the world of missionary work, which remained underappreciated at a time when a gender-based hierarchy played a defining role, and is still uncelebrated today.
Keywords: Women missionaries -- United States -- History.